The Complete Chloroplast Genome of Euphrasia regelii, Pseudogenization of ndh Genes and the Phylogenetic Relationships Within Orobanchaceae - Zhou, Tao; Ruhsam, Markus; Wang, Jian; Zhu, Honghong; Li, Wenli; Zhang, Xiao; Xu, Yucan; Xu, Fusheng; Wang, Xumei (Frontiers in Genetics, 2019)
Euphrasia (Orobanchaceae) is a genus which is widely distributed in temperate regions of the southern and northern hemisphere. The taxonomy of Euphrasia is still controversial due to the similarity of morphological characters and a lack of genomic resources. Here, we present the first complete chloroplast (cp) genome of this taxonomically challenging genus. The cp genome of E. regelii consists of 153,026 bp, including a large single-copy region (83,893 bp), a small single-copy region (15,801 bp) and two inverted repeats (26,666 bp). There are 105 unique genes, including 71 protein-coding genes, 30 tRNA and 4 rRNA genes. Although the structure and gene order is comparable to the one in other angiosperm cp genomes, genes encoding the NAD(P)H dehydrogenase complex are widely pseudogenized due to mutations resulting in frameshifts, and stop codon positions. We detected 36 dispersed repeats, 7 tandem repeats and 65 simple sequence repeat loci in the E. regelii plastome. Comparative analyses indicated that the cp genome of E. regelii is more conserved compared to other hemiparasitic taxa in the Pedicularideae and Buchnereae. No structural rearrangements or loss of genes were detected. Our analyses suggested that three genes (clpP, ycf2 and rps14) were under positive selection and other genes under purifying selection. Phylogenetic analysis of monophyletic Orobanchaceae based on 45 plastomes indicated a close relationship between E. regelii and Neobartsia inaequalis. In addition, autotrophic lineages occupied the earliest diverging branches in our phylogeny, suggesting that autotrophy is the ancestral trait in this parasitic family.